2011
DOI: 10.1590/s0100-55022011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de álcool entre estudantes de faculdades de Medicina de Minas Gerais, Brasil

Abstract: III PALAVRAS-CHAVE:-Consumo de Bebidas Alcoólicas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
43

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 12 publications
3
8
0
43
Order By: Relevance
“…In the present study, 34.1% of the students reported abstinence from alcohol, while 65.9% had consumed alcoholic beverages within the previous year. Studies that used the same instruments to measure alcohol consumption among female university students in Minas Gerais, obtained similar results to the current study: 36.4% of abstinence and 63.6% of alcohol consumption among medical students 26 and 71.5% of regular alcohol consumption among health sciences students. 8 In Mexico, medical students also presented a prevalence of alcohol consumption (62.3%) 5 similar to that observed here in Aracaju.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, 34.1% of the students reported abstinence from alcohol, while 65.9% had consumed alcoholic beverages within the previous year. Studies that used the same instruments to measure alcohol consumption among female university students in Minas Gerais, obtained similar results to the current study: 36.4% of abstinence and 63.6% of alcohol consumption among medical students 26 and 71.5% of regular alcohol consumption among health sciences students. 8 In Mexico, medical students also presented a prevalence of alcohol consumption (62.3%) 5 similar to that observed here in Aracaju.…”
Section: Discussionsupporting
confidence: 85%
“…Research conducted with medical students in the southeast of Brazil found 25.2% of at-risk alcohol consumers and 74.8% of abstinent or low-risk consumers. 26 The highest percentage of alcohol consumption at problematic levels was found in Mexican medical students (46.0%). 5 In the latter two studies, the prevalence of at-risk use was higher than the present study probably because male students were included in the samples.…”
Section: Discussionmentioning
confidence: 95%
“…Um trabalho realizado em mais de cem cidades brasileiras com mais de 200 mil habitantes apontou que o consumo de álcool é muito relevante na faixa etária de 18 a 24 anos e que 15,5% dessa população referem dependência 17 . Entre estudantes de Medicina, esse percentual variou de 25% de consumo exagerado até 98% em algumas regiões, dependendo da amostra e da forma de coleta dos dados [18][19][20] . Além da elevada prevalência de consumo, há uma preocupação importante com o uso exagerado de álcool e embriaguez.…”
Section: Discussionunclassified
“…Por outro lado, ter religião e relacionamento fixo atuou como protetor desse consumo. Entre estudantes de Minas Gerais, a prevalência do consumo de álcool foi de 60%, e 25% destes referiram a necessidade de buscar programas para prevenir danos causados pelo consumo abusivo de bebida alcoólica 19 . Apesar da alta prevalência de experimentação de álcool e até mesmo de embriaguez, registrada em todos os períodos avaliados, a dependência de álcool referida pelos estudantes foi muito baixa, independentemente do período avaliado.…”
Section: Discussionunclassified
“…It is clear, therefore, the severe association of using SPA and the development of mental disorders [21].…”
Section: Discussionmentioning
confidence: 99%